Targeting and Impact of National Health Insurance Program in Indonesia - galih putri yunistria (Economics Development Analysis Journal, 2020)
National Health Insurance System (NHIS) program in Indonesia has been launched since 2014,and government spending to support the program has allocated nearly 40% of MoH budget,especially for the NHIS subsidies. This study examined the distribution of NHIS subsidizedbeneficiaries which associated with the household income distribution, and also studied about theutilization rate of health care facilities among the residents since the NHIS program has introducedto change citizens’ health seeking behaviour from traditional services to health facilities. Using the2016 Susenas data, this study employed the benefit incidence analysis method to measure thedistribution of NHIS-subsidized group, and logistic regression analysis to determine the health careseeking behavior. The result shows that households in higher income (quantile III-V) get benefitfrom government subsidy on NHIS program. It indicated there was a leakage on governmentbudget that not belong to the target (quantile I and II). Then, logistic regression analysis found thatpeople with higher income and having health insurance tend to visit health care facilities morefrequently than lower income group and uninsured people. This can be concluded that healthinsurance ownership is one of the important factors to influence people visiting health carefacilities.